2014
DOI: 10.1007/s11187-014-9571-7
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect information and labor market bias against small and medium-sized enterprises: a Korean case

Abstract: In this study, we examine the labor market's bias against small and medium-sized enterprises focusing on the Seoul Digital Industrial Complex case. We adopt Heckman's approach to control selection bias, and use primary data from questionnaire surveys conducted at both firm and employee levels. We find that conventional firm-specific factors, such as wages, fringe benefits, and weekly work hours, primarily explain the labor market bias, but imperfect information is also positively associated with the bias. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Therefore, it is necessary to first select fields that can be improved, establish strategies, and determine practical and workable strategies for SMEs, while simultaneously addressing negative SME's perceptions among young job seekers (De Wit & De Kok, 2014;Park et al, 2014).…”
Section: Studies On Employment In Small-and Medium-sized Enterprisesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is necessary to first select fields that can be improved, establish strategies, and determine practical and workable strategies for SMEs, while simultaneously addressing negative SME's perceptions among young job seekers (De Wit & De Kok, 2014;Park et al, 2014).…”
Section: Studies On Employment In Small-and Medium-sized Enterprisesmentioning
confidence: 99%
“…Proceedings of the 25th ACM SIGKDD international conference on knowledge discovery & data mining. Yang, J., Hwang, S., & Kim, S. (2014). Analysis of the determinants of employment and turnover in local smalland medium-sized enterprises (SMEs) of local university graduates.…”
Section: Limitation and Future Researchmentioning
confidence: 99%
“…There have been conflicting arguments for this variable. Park et al [66] and Choi and Lee [67] claimed that joint research experience increased the implementation of technology commercialization. However, Saavedra and Bozeman [68] and Park et al [69] concluded that the development of research institutions and companies should be separate.…”
Section: Control Variablesmentioning
confidence: 99%
“…As a result, the effects of HRM missteps in hiring, evaluating, developing, firing, etc., are likely amplified in SMEs where there are fewer “places to hide” (Messersmith and Guthrie, 2010). Evidence of his notion can be found in research which demonstrates that SMEs face unique HRM challenges with respect to retaining employees (De Clercq and Rius, 2007), which is compounded by the fact that SMEs simultaneously face difficulty in recruiting new employees (Park et al , 2014).…”
Section: Sme Hrm Formalization Social Exchanges and Tilmentioning
confidence: 99%